Other people's children eaudiobook A novel. - Hoffmann, Jeff (Simon & Schuster Audio, 2021)
An "engrossing debut" (Laura Dave, New York Times bestselling author of The Last Thing He Told Me ) novel about a couple whose baby dreams of adoption push them to do the unthinkable when their baby's birth family steps into the picture. How far would you go to save your family? As soon as Gail and John Durbin bring home their adopted baby Maya, she becomes the glue that mends their fractured marriage. But the Durbin's social worker, Paige, can't find the teenage birth mother to sign the consent forms. By law, Carli has seventy-two hours to change her mind. Without her signature, the adoption will unravel. Carli is desperate to pursue her dreams, so giving her baby a life with the Durbins' seems like the right choice—until her own mother throws down an ultimatum. Soon Carli realizes how few choices she has. As the hours tick by, Paige knows that the Durbins' marriage won't survive the loss of Maya, but everyone's life is shattered when they—and baby Maya—disappear without a trace. Filled with heartrending turns, Other People's Children is a "heartbreakingly dark, suspenseful exploration of the boundaries two women push to have a child" (Cara Wall, bestselling author of The Dearly Beloved ) that you'll find impossible to put down.